Науково-технічні аспекти інтеграції ОЕС України до об’єднання енергосистем європейських держав ENTSO-E - Жаркін, А.Ф.; Павловський, В.В.; Лук'яненко, Л.М. (Технічна електродинаміка, 2012)
The main scientific and technical aspects of connection of the Ukraine's IPS to the synchronous area of ENTSO-E are considered. The most important problems are designated: stability of whole IPS of Ukraine and its border areas, congestion of power plants interfaces in border area, flexible voltage and reactive power control, update the IPS of Ukraine restoration plan after blackouts, the appropriate level of power quality and electromagnetic compatibility. Finding the solution of these problems is one of the necessary conditions for realization of integration of Integrated Ukrainian Power System to ENTSO-E.